Profile of College Students' Critical Thinking Skills Assisted by Problem-Based Learning Models on Electromagnetic Material - Mas Al Fath Imru'ul Qais As-Syauqi; Fida Rachmadiarti; Raharjo Raharjo; Mohammad Budiyanto (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2024)
Objective: This research aims to analyze the profile of students' critical thinking abilities in physics learning, especially electromagnetic material, with the help of a problem-based learning model implemented at a university in Surabaya, Indonesia. Method: The research method used was included in preliminary research with a sample of 19 students. Data collection techniques use critical thinking skills tests, student response questionnaires, and lecturer interviews. Then, the data was analyzed using qualitative descriptions to represent the research results. Results: Analysis shows students' critical thinking skills are still relatively low. Critical thinking indicators that get an average score from high to low are interpretation, analysis, inference, and evaluation. An alternative that can be done to increase students' interest and critical thinking skills is to apply the PBL model in physics learning. Novelty: The novelty of this research lies in its new contribution to mapping students' initial abilities regarding their critical thinking skills with the help of the PBL model. This mapping helps lecturers evaluate physics learning, especially electromagnetic material, and determine what future steps can be taken to improve students' critical thinking skills.